Applying metaheuristic approaches on the single facility location problem with polygonal barriers. (2014) - Gharravi, Hossein Gharehmeshk; Farham, Mohammad Saleh
In this paper, we describe, improve, and compare the performance of four metaheuristic algorithms on the single facility location problem with barriers. The barriers are polygonal regions on a plane where neither facility location nor travelling is permitted. The objective function in this problem is non-convex justifying the application of metaheuristics and their robustness. We argue that this problem has interesting geometric properties such as size and distribution of barriers on the plane which can affect the choice of metaheuristics. Various test instances which reflect these geometric properties are designed in this paper. Through computational experiments, we discuss the effect of these properties on different variants of metaheuristics and propose the suitable metaheuristic and parameter setting for the single facility location problem with barriers.